To Compare Outcomes of Stainless Steel Skin Staples and Polypropylene Sutures for Mesh Anchoring in Lichtenstein Tension Free Inguinal Hernia Repair - Bahri Room; Suliman Shah; Fazli Junaid; Noor Sardar Afridi; Rafat ullah; Yasir Hussain (Journal of Liaquat University of Medical & Health Sciences, 2026)
OBJECTIVE: This study aimed to compare the outcome of Lichtenstein inguinal hernia repair using stainless steel staples versus polypropylene sutures for mesh anchorage. METHODOLOGY: A Prospective analytical study was conducted at the Surgical Department Lady Reading Hospital, Peshawar, from June to December 2022. Consecutive non-probability sampling was used to assess a total of 100 cases (50 undergoing repair by each method). The study included primary unilateral inguinal hernia cases aged 20 to 70 years. Patients with complicated inguinal hernia, chronic ailments, BMI > 30, or immunocompromised state were excluded to avoid confounders. Outcome was assessed in terms of operative time, postoperative pain, and surgical site infection. RESULTS: Surgical site infections (SSI) were noted in 6% cases of Group A and 16% cases of Group B (with p-value = 0.11). The only parameter that showed a statistically significant difference between the two groups was operative time (Group A: 36.63 ± 3.14 minutes, Group B: 45.68 ± 2.69 minutes, p-value <0.001). The differences in postoperative pain between the two groups were not statistically significant (p-value of 0.47). CONCLUSION: Both techniques provide excellent results. However, mesh anchoring using stainless steel staples takes less time than the polypropylene anchoring, which can have essential implications in postoperative recovery.